Comparison of homogenization with the GentleMacs Dissociator vs conventional methods for routine tissue processing. (1st May 2022) - Pradal, M.; Saint‐sardos, P.; Faïs, T.; Bonnet, R.; Delmas, J.
Abstract: Tissue specimens are valuable materials for microbiological diagnosis. The method of tissue processing can have a significant effect on sensitivity. This study aimed to compare different biopsy processing methods in terms of efficacy and standardization. Pork tissue artificially inoculated with Staphylococcus aureus and Escherichia coli, and samples of infected human tissue were processed by different methods before culture, and the results compared. Bacterial recovery from artificially inoculated pork tissue was significantly higher by homogenization with GentleMacs Dissociator than with sonication. No significant difference was observed between the GentleMacs Dissociator and manual treatment with a scalpel and vortexing. The microbial yield from homogenized human tissues was significantly higher after homogenization with GentleMacs Dissociator than with the conventional method. Homogenization with the GentleMacs Dissociator retrieves bacteria from tissue effectively. Tissue homogenization with the Dissociator is easy and fast to perform and allows for a high degree of standardization. Abstract: Significance and Impact of the Study: Standardization and harmonization of medical laboratories methodologies is essential. The method for processing human tissue and pus samples using the GentleMACS Dissociator is easy and fast to perform and allows for a high degree of standardization while ensuring that bacteria are well‐detected.